2013
DOI: 10.1038/onc.2013.508
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of FOXA1 facilitate androgen receptor chromatin binding resulting in a CRPC-like phenotype

Abstract: Castration-resistant prostate cancer (CRPC) continues to pose a significant clinical challenge with new generation second line hormonal therapies affording limited improvement in disease outcome. As the androgen receptor (AR) remains a critical driver in CRPC, understanding the determinants of its transcriptional activity is important for developing new AR targeted therapies. FOXA1 is a key component of the AR transcriptional complex yet its role in prostate cancer progression and the relationship between AR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 53 publications
7
68
0
Order By: Relevance
“…In PCa xenograft models, larger tumors are induced upon FOXA1 overexpression, suggesting that FOXA1 amplification may have functional consequences in clinical disease (52). In PCa cells, FOXA1 overexpression increases proliferation rates under low-androgen conditions (103). This phenotype is linked to the FOXA1-dependent acquisition of new AR genomic binding sites that activate a novel, CRPC-like transcriptional profile activation and prevents transcription.…”
Section: Alterations In Collaborating Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In PCa xenograft models, larger tumors are induced upon FOXA1 overexpression, suggesting that FOXA1 amplification may have functional consequences in clinical disease (52). In PCa cells, FOXA1 overexpression increases proliferation rates under low-androgen conditions (103). This phenotype is linked to the FOXA1-dependent acquisition of new AR genomic binding sites that activate a novel, CRPC-like transcriptional profile activation and prevents transcription.…”
Section: Alterations In Collaborating Factorsmentioning
confidence: 99%
“…that is enriched in oncogenic signaling pathways known to promote cell growth and survival in a hormone-starved environment (103). FOXA1 amplification and copy number gain are seen in 20% of primary BCa (Table 1 and refs.…”
Section: R E V I E W S E R I E S : N U C L E a R R E C E P T O R Smentioning
confidence: 99%
“…Amplification and overexpression of FOXA1 have been detected in primary tumors but is more common in metastatic CRPC, highlighting its role in persistent AR signaling in the castrate state (Jain et al 2011, Grasso et al 2012, Cancer Genome Atlas Research 2015, Robinson et al 2015, Kumar et al 2016. Overexpression of FOXA1 has been associated with poor outcome and AR expression (Jain et al 2011, Sahu et al 2011, Gerhardt et al 2012, Robinson et al 2014. Mechanistically, high levels of FOXA1 in tumor cells may enhance AR:chromatin interactions when androgen levels are low and also enable binding of AR to non-canonical sites, both of which can drive a CRPC gene expression program , Robinson et al 2014.…”
Section: Ar Coregulator Alterations In Crpcmentioning
confidence: 99%
“…Overexpression of FOXA1 has been associated with poor outcome and AR expression (Jain et al 2011, Sahu et al 2011, Gerhardt et al 2012, Robinson et al 2014. Mechanistically, high levels of FOXA1 in tumor cells may enhance AR:chromatin interactions when androgen levels are low and also enable binding of AR to non-canonical sites, both of which can drive a CRPC gene expression program , Robinson et al 2014. Interestingly, the converse also appears to be true: a number of studies have found that loss of FOXA1 can enable androgen-independent AR chromatin binding at non-canonical sites throughout the genome, and this cistromic reprogramming has been associated with enhanced AR signaling in CRPC (Sahu et al 2011, Jin et al 2014.…”
Section: Ar Coregulator Alterations In Crpcmentioning
confidence: 99%
“…β-Catenin can also interact with FOXO transcriptional factors in response to oxidative stress to promote cells exit from the cell cycle and entry into cell quiescence [72]. FOXA1 was shown to be overexpressed in advanced prostate cancer and metastases, and over expression of FOXA1 led to enrichment of the Wnt signaling pathway [73]. Heterogeneous nuclear ribonucleoprotein K (HnRNP K) was also found to be overexpressed in prostate cancer tissues and overexpression of HnRNP K positively associated with high Gleason score and poor prognosis [74,75].…”
mentioning
confidence: 99%